Indicative financial premium created through quality service and good customer relationship in a South African hydrocarbon engineering business - Cowan, Thomas (My University, 2016)
ABSTRACT Increasing profit margins within companies have been studied for many years. Various ways of improving profits have been considered, but a limited amount of work has been done to determine the influence quality of service delivery and customer relationship has on the company’s profit margins. The objective of this study is thus to determine the financial premium that can be generated by service companies through delivering quality service and having a strong customer relationship. As part of the research, two groups of five candidates each were interviewed by means of semi-structured interviews. The groups represented the customer and the service companies respectively. A qualitative approach was used to capture and evaluate the data. The findings were recorded, reduced and compared to the results of the literature study conducted. The findings in this research indicate that both customers and service companies support the idea of creating a long-term relationship through quality of service. Both groups interviewed support the conclusion of the literature study that a financial premium can be generated through quality of service and a strong customer relationship. Co-creating value with the customer as well as value adding practices contributed to the premiums that can be generated with branding, with length of service contributing less.
M.B.A. Thesis
Keywords: Customer services -- South Africa, Customer relations -- Management.